Optical filters and resonant cavities based on di-ureasil organic–inorganic hybrids - Vicente, Carlos Miguel Santos; Ferreira, Rute Amorim Sá; Pecoraro, Édison [UNESP]; André , Paulo Sergio de Brito; Carlos, Luís Dias (Springer Nature, 2011)
Sol–gel derived poly(oxyethylene)/siloxane organic–inorganic di-ureasil hybrids containing different amounts (20–60% mol) of methacrylic acid (McOH) modified zirconium oxo-clusters (Zr-OMc) were processed as thin films and transparent and shape controlled monoliths. Laser direct writing was used to create channel waveguides, Bragg gratings, Fabry–Perot cavities and optical filters. The resulting Fabry–Perot optical cavity displays a free spectral range of 16.55 GHz and a fringe intensity contrast of 5.35 dB. Optical rejection values between 6.7 and 10.4 dB were obtained by varying the amount of the Zr-OMc oxo-clusters.
Keywords: Organic–inorganic hybrids; Integrated optics; Sol–gel; Waveguides; Fabry–Perot cavities; Optical filters